LITERATURE REVIEW DISCLOSURE CORPORATE SOCIAL RESPONSIBILITY (CSR) OFIN ASSESSING COMPANY PERFORMANCE - Riri Mayliza (International Journal on Economics, Finance and Sustainable Development, 2021)
Companies in carrying out business activities in the implementation process, of course, will be related to social responsibility towards the environment. CSR, which should have been in the voluntary domain, is now being brought into the mandatory domain. In addressing this, companies must be able to translate CSR in a logical framework to provide benefits for sustainable company performance. This study is a literature study from various empirical studies on corporate social responsibility and corporate performance. The results of this literature indicate that the results of the impact of company activities on the environment on the wider community, which are implemented with good governance, are a necessity for companies to be able to run their business. Which if it can be done properly through a CSR program that can meet community expectations of its existence, it will have a good impact on company performance